Protective effects of Pelargonium graveolens (geranium) oil against cefotaxime-induced hepato-renal toxicity in rats - Azzam, Shaimaa M.; Elsanhory, Heba M. A.; Abd El-Slam, Ahmed H.; Diab, Marwa S. M.; Ibrahim, Halima Mohamed; Yousef, Abdalrahman Mohammed; Sabry, Fatma Mahmoud; Khojah, Ebtihal Y.; Bokhari, Somaiah A.; Salem, Gad Elsayed Mohamed; Zaghloul, Marwa Saad (Frontiers in Toxicology, 2024)
Cefotaxime is a broad-spectrum antibiotic targeting Gram-negative bacteria used for diverse infections, but it can be toxic to the stomach, liver, and kidneys. This study explored the protective effects of geranium oil against cefotaxime-induced hepatotoxicity and nephrotoxicity in rats, employing biochemical, histopathological, and immunohistochemical evaluations. Thirty rats were divided into five groups of six animals each one. Group 1 received orally normal saline for 14 days, Group 2 was given orally 2.5% DMSO for 14 days, Group 3 received cefotaxime (200 mg/kg/day IM) for 14 days, Group 4 received with cefotaxime (200 mg/kg/day IM) and geranium oil (67 mg/kg b. w./day orally in DMSO) for 14 days, and Group 5 received geranium oil alone (67 mg/kg b. w./day orally in DMSO) for 14 days. Geranium oil significantly reduced cefotaxime-induced damage, evidenced by lower serum levels of liver enzymes (AST, ALT), renal markers (urea, creatinine), and other indicators (alkaline phosphatase, TNF-alpha, IL-1Beta, MAPK, nitric oxide, MDA). It also increased levels of protective tissue biomarkers such as NrF2, albumin, catalase, Beclin 1, and reduced glutathione (GSH). Histopathological and immunohistochemical analyses revealed significant protective effects in liver and renal tissues in rats treated with Geranium oil. These results suggest that Geranium oil is effective in mitigating cefotaxime-induced hepatotoxicity and renal toxicity.